Online Gambling Regulatory Policy: An Analysis from the Perspective of the Rights and Duties of the Gambler in Portugal - Catarino, João Ricardo; Machado, Carlos Henriques (LeXonomica, 2025)
Online games constitute an increasingly widespread activity that carries increased risks for players, especially minors. This study analyses the effectiveness of protecting online players' rights considering Portuguese legislation, which originates from the common European rules established for all Member States of the European Union. This study aims to characterise the Portuguese regulatory policy for games of chance, especially in the online gaming modality, its regulatory principles, its characteristics, and purposes, and to describe how it articulates with European recommendations. Based on this characterisation, this study analyses the effectiveness of compliance with the fundamental aspects of this regulatory policy by entities operating online gambling from the perspective of protecting the rights and duties of players, as enshrined. It concludes that some of these rights need to be sufficiently protected. The methodology includes analysing the websites of licensed entities and providing a questionnaire to young people who frequently play online. The study shows that the information on online gaming platforms reasonably complies with the current legal requirements and that players must be fully aware of all their rights. It also highlights that such rights are not fully protected in sensitive aspects.Povzetek članka v slovenskem jeziku (abstract in Slovene language)Spletne igre so vse bolj razširjena dejavnost, ki prinaša večja tveganja za igralce, zlasti mladoletnike. Ta študija analizira učinkovitost zaščite pravic spletnih igralcev ob upoštevanju portugalske zakonodaje, ki izhaja iz skupnih evropskih pravil, določenih za vse države članice Evropske unije. Namen te študije je opisati portugalsko regulativno politiko za igre na srečo, zlasti na področju spletnih iger na srečo, njena regulativna načela, značilnosti in namene ter opisati, kako se ujema z evropskimi priporočili. Na podlagi te opredelitve ta študija analizira učinkovitost upoštevanja temeljnih vidikov te regulativne politike s strani subjektov, ki prirejajo spletne igre na srečo, in z vidika varstva pravic in dolžnosti igralcev. Ugotavlja, da je treba nekatere od teh pravic zaščititi v zadostni meri. Metodologija vključuje analizo spletnih strani licenciranih subjektov in posredovanje vprašalnika mladim, ki pogosto igrajo na spletu. Študija kaže, da so informacije na spletnih igralnih platformah v razumni meri skladne z veljavnimi zakonskimi zahtevami in da se morajo igralci v celoti zavedati vseh svojih pravic. Poudarja tudi, da te pravice v občutljivih vidikih niso v celoti zaščitene.